Pelaksanaan Sistem Pengelolaan Penilaian Angka Kredit Dosen Kopertais Wilayah Xi Kalimantan - A Arbani; Muhammad Akbar (Administraus, 2019)
This study aims: (1) to find out and explore the management system of credit score assessments for increasing lecturers' functional positions in the Kopertais Region XI Kalimantan environment; (2) describe the factors that influence the management of the credit score for lecturers' functional positions; (3) outline the solutions made to obstacles in the management process of assessing functional position credit numbers for lecturers at Kopertais Region XI Kalimantan. This study used a qualitative descriptive approach with the research locus of Kopertais Region XI Kalimantan. The source of the data is the leadership and staff of Kopertais Region XI Kalimantan who are responsible and in charge of the assessment of lecturer credit numbers, as well as the assigned Assessment Team. Data collection is done by observation, in-depth interviews, and documentary studies. The validity of the data is tested through a process of credibility, dependability, and confirmation. Data analysis using the Miles & Huberman model carried out during the process of data collection and research takes place through three stages, namely data reduction, data presentation, and conclusion or verification. The results of this study indicate that: (1) The process of managing the credit score assessment of Kopertais lecturers in Region XI Kalimantan consists of three stages, namely the pre-assessment stage (according to the Standard Operating Procedure), the assessment stage (by the Assessment Team), and post-assessment stages (filing for Determination of Decree of Decision by administrative staff); (2) Some factors or constraints that affect the assessment management process: often late in the proposal, incomplete proposal file, lack of staff processing assessment, lack of work facilities and infrastructure owned, lack of understanding of lecturers on functional positions, etc.; (3) Efforts to overcome: increase staff administration of credit score assessment processes (contract workers), strengthening procedures and division of labor (job description and SOP), and conducting workshops or technical guidance for the proposed functional positions of lecturers. Conclusion: Management of lecturers' credit score assessment on Kopertais Region XI Kalimantan area has been going well, the main obstacle is still the availability and competency of the human resources involved in it. Suggestion: it is necessary to add and increase the competence of administrative and socialization staff and on going technical guidance for the appointment of lecturer functional positions. Penelitian ini bertujuan: (1) untuk mengetahui dan mengeksplorasi sistem pengelolaan penilaian angka kredit untuk kenaikan jabatan fungsional dosen di lingkungan Kopertais Wilayah XI Kalimantan; (2) mendeskripsikan faktor-faktor yang mempengaruhi pengelolaan penilaian angka kredit jabatan fungsional dosen; (3) menguraikan solusi yang dilakukan terhadap hambatan dalam proses pengelolaan penilaian angka kredit jabatan fungsional dosen Kopertais Wilayah XI Kalimantan. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan lokus penelitian Kopertais Wilayah XI Kalimantan. Sumber data adalah pimpinan dan staf Kopertais Wilayah XI Kalimantan yang bertanggungjawab dan membidangi urusan penilaian angka kredit dosen, serta Tim Penilai yang telah ditetapkan. Pengumpulan data dilakukan dengan cara observasi, wawancara mendalam, dan studi dokumenter. Keabsahan data diuji melalui proses kredibilitas, dependabilitas, dan konfirmabilitas. Analisis data menggunakan model Miles & Huberman yang dilakukan selama proses pengumpulan data dan penelitian berlangsung melalui tiga tahapan, yakni reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil Penelitian ini menunjukkan bahwa: (1) Proses pengelolaan penilaian angka kredit dosen Kopertais Wilayah XI Kalimantan terdiri dari tiga tahapan, yakni tahapan pra penilaian (sesuai Standar Operasional Prosedur), tahapan penilaian (oleh Tim Penilai), dan tahapan pasca penilaian (pemberkasan untuk penetapan Surat Keputusan penilaian oleh staf administrasi); (2) Beberapa faktor atau kendala yang mempengaruhi proses pengelolaan penilaian: sering terlambatnya usulan, kurang lengkapnya berkas usulan, kurangnya jumlah staf yang memproses penilaian, kurangnya sarana dan prasarana kerja yang dimiliki, kurangnya pemahaman dosen terhadap jabatan fungsional, dan lain-lain; (3) Upaya mengatasi: menambah staf administasi pemeroses penilaian angka kredit (tenaga kontrak), penguatan tatacara dan pembagian kerja (job description dan SOP), dan pelaksanaan workshop atau bimbingan teknis untuk pengusulan jabatan fungsional dosen. Kesimpulan: Pengelolaan penilaian angka kredit dosen pada Kopertais Wilyah XI Kalimantan sudah berjalan dengan baik, kendala utama masih pada ketersediaan dan kompetensi sumber daya manusia yang terkait di dalamnya. Saran: perlu penambahan dan peningkatan kompetensi tenaga adminsitrasi, sarana dan prasarana, dan pelatihan penyusunan angka kredit serta sosialisasi yang berkelanjutan untuk pengusulan jabatan fungsional dosen.